INCREASING THE ECONOMIC EFFICIENCY OF CLOTHING ENTERPRISES IN UZBEKISTAN - Ахмедова Газиза Азимкызы (Modern American Journals, 2025)
This article is devoted to the study of ways to improve the economic efficiency of clothing manufacturing enterprises in the Republic of Uzbekistan. The work analyzes the key factors affecting the profitability of clothing industry enterprises, identifies the main problems of the industry and proposes strategic solutions for optimizing production processes. Particular attention is paid to the issues of equipment modernization, implementation of innovative technologies, improvement of the quality management system and development of export potential. The results of the study of the current state of the clothing industry of Uzbekistan are presented, the prospects for integrating enterprises into global value chains are considered. Based on the conducted analysis, a comprehensive model for increasing the economic efficiency of enterprises is proposed, taking into account the specifics of the national economy and global trends in the development of the fashion industry.
Keywords: Clothing industry, Uzbekistan, economic efficiency, production optimization, textile cluster, innovative technologies, export potential, competitiveness.